2015
DOI: 10.4172/2165-7092.s5-004
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia in Pancreatic beta Cells

Abstract: Sleep apnea syndrome (SAS) a highly prevalent disorder, and characterized by repetitive episodes of intermittent hypoxia (IH), i.e. recurrent episodes of oxygen desaturation during sleep, the development of daytime sleepiness, and deterioration in the quality of life. Multiple epidemiological studies have provided evidence implicating the presence of SAS as a risk factor for insulin resistance and type 2 diabetes and have reported that type 2 diabetes is associated with SAS independently of age, sex, and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Experimental models of IH, both in vitro and in vivo, include a variety of oxygen concentrations and exposure times. We and others have previously reported that the magnitude of IH expressed by SpO 2 fluctuates between 75-98% and 50-80% in SAS [17,103,104], which is almost equivalent to the medium condition in our studies. Under our experimental 'IH' or 'normoxia' condition, cells were exposed either to IH (5 min [5% CO 2 1% O 2 ]/10 min [5% CO 2 21% O 2 ]) or normoxia for 24 h [5,7,19,25,32].…”
Section: Differences In Experimental Ih Conditions In Vitro and In Vivosupporting
confidence: 81%
“…Experimental models of IH, both in vitro and in vivo, include a variety of oxygen concentrations and exposure times. We and others have previously reported that the magnitude of IH expressed by SpO 2 fluctuates between 75-98% and 50-80% in SAS [17,103,104], which is almost equivalent to the medium condition in our studies. Under our experimental 'IH' or 'normoxia' condition, cells were exposed either to IH (5 min [5% CO 2 1% O 2 ]/10 min [5% CO 2 21% O 2 ]) or normoxia for 24 h [5,7,19,25,32].…”
Section: Differences In Experimental Ih Conditions In Vitro and In Vivosupporting
confidence: 81%
“…The As4.1 cells and human embryonic kidneyderived HEK293 cells were grown in Dulbecco's Modified Eagle Medium (FUJIFILM Wako Pure Chemical Corporation, Osaka, Japan) containing 10% (v/v) fetal calf serum (FCS), 100 units/mL penicillin G (FUJIFILM Wako), and 100 µg/mL streptomycin (FU-JIFILM Wako), as described in prior studies [9,40,41]. The cells were exposed to either normoxia (21% O 2 , 5% CO 2 , and balanced N 2 ) or IH (70 cycles of 5 min sustained hy-poxia (1% O 2 , 5% CO 2 , and balanced N 2 ) and 10 min normoxia) in a custom-designed, computer-controlled incubation chamber attached to an external O 2 -CO 2 -N 2 computerdriven controller (O 2 programmable control, 9200EX, Wakenyaku Co., Ltd., Kyoto, Japan), as described in previous works [37,[42][43][44][45][46]. We used this in vitro model of IH, which resulted in fluctuations in the pressure of oxygen similar to the IH condition observed in patients with severe SAS, to repeatedly exposed the cells to severe hypoxemia followed by mild hypoxemia or normoxia (i.e., IH) [47].…”
Section: Cell Culturementioning
confidence: 99%
“…We used this in vitro model of IH, which resulted in fluctuations in the pressure of oxygen similar to the IH condition observed in patients with severe SAS, to repeatedly exposed the cells to severe hypoxemia followed by mild hypoxemia or normoxia (i.e., IH) [47]. We have previously reported that the magnitude of the IH expressed by SpO 2 fluctuated between 75% and 98% and 50% and 80% in patients with SAS [42,45,46], which was nearly equivalent to the medium condition in the present study.…”
Section: Cell Culturementioning
confidence: 99%
“…How similar/different to/from SAS patients are problems in in vitro system. Although the O 2 concentrations of in vitro system is similar to IH patients and the in vitro system can examine direct effects of IH excluding effects of other organs and cells, 71 the results from in vitro system sometimes are different from that occur in SAS patients. Therefore, our results obtained in this study indicated a possible occurrence in SAS patients and clinical studies using SAS patients are required.…”
Section: Discussionmentioning
confidence: 99%